2021
DOI: 10.1111/jfpp.15384
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of aflatoxin producing molds by selected and broadband infrared wavelength treatments, and the effects of the treatments on rice milling quality

Abstract: This study investigated the impacts of selected and broadband infrared (IR) wavelength treatments with tempering step on inactivation of aflatoxigenic molds and the treatments' effects on head rice yield (HRY). Rough rice was treated with different IR intensities, product-to-emitter gaps, and heating durations. Afterward, the samples were tempered at 60°C for 4 hr. Selected IR wavelength treatment at intensities of 15.71 and 10.08 kW/m 2 for 20 and 30 s resulted in complete aflatoxigenic mold inactivation; bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…In all the treatments, the chalkiness of rice was not significantly affected. Although, in our previous studies (Oduola et al, 2020; Oduola & Atungulu, 2021), IR wavelength of 3.2 μm had significant effects on reducing the microbial population on rice, this study showed its negative impact on rice color and pasting properties. Therefore, it is important to optimize the processing parameters involving IR wavelength 3.2 μm to prevent its adverse effect on rice quality; this holds a huge prospect and may be useful in rice and other grains processing.…”
Section: Resultscontrasting
confidence: 64%
“…In all the treatments, the chalkiness of rice was not significantly affected. Although, in our previous studies (Oduola et al, 2020; Oduola & Atungulu, 2021), IR wavelength of 3.2 μm had significant effects on reducing the microbial population on rice, this study showed its negative impact on rice color and pasting properties. Therefore, it is important to optimize the processing parameters involving IR wavelength 3.2 μm to prevent its adverse effect on rice quality; this holds a huge prospect and may be useful in rice and other grains processing.…”
Section: Resultscontrasting
confidence: 64%